Pengaruh Karakteristik Dewan Direksi terhadap Kinerja Bank Syariah - Rizki Audio; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to examine the effect of the characteristics of the board of directors on the performance of Islamic banks. This study examines the characteristics of the board of directors in proxy size of the board of directors, remuneration of the board of directors, frequency of board of directors meetings, age of the board of directors, educational background of the board of directors. This study uses a sample of Islamic banking registered with the OJK from 2015-2016. The results of this study found that the remuneration of the board of directors has a positive effect on the performance of Islamic banks, while the size of the board of directors, the frequency of board of directors meetings, the age of the board of directors, the educational background of the board of directors does not affect the performance of Islamic banks.